The Relationship between Risk Management on Problematic Asset Purchase Decisions in Indonesia - Puspitasari, Devy M.; Napitupulu, Sotarduga; Roespinoedji, Djoko; Utami, Eristy M.; Nursyanti, Farida (CENTRAL ASIA AND THE CAUCASUS, 2022)
Purpose: This study aims to know the relationship between risk management on problematic asset purchase decisions in Indonesia.Design/methodology/approach: Partial Least Square (PLS). The unit of analysis used in this research is the executive decision makers in purchasing problem assets during period 2016-2019. The sampling method of this unit of analysis is based on the purposive sampling method. Respondents taken in this study include executives who buy troubled assets in Indonesia with a wide variety of information, which are expected to be more varied and detailed, so that in the end the research results will be obtained as expected. Executives at the level of company owners and top management of the company.Findings: The results showed that risk management has a direct effect on the purchase decision of problematic assets. Efforts to develop decision-making in purchasing assets from non-performing loans need to pay attention to the utilization of risk understanding in order to obtain the right purchasing decisions.Originality/value: This research will be useful in knowing that the implementation of good risk management can ensure business sustainability, especially in assets that are relatively high risk.